Analisis Deskriptif Kuantitatif Tingkat Kepuasan Layanan e-Perpus Kota Depok Berbasis PIECES Framework - Fathiyah Faiha Adwa; Nurul Janah; Akhmam Fahmi (DBESTI: Journal of Digital Business and Technology Innovation, 2026)
The Department of Archives and Library Services of Depok City has introduced a digital library service through the e-Perpus Kota Depok mobile application. This study aims to assess user satisfaction based on the quality of services provided. The PIECES Framework, comprising 6 dimensions: Performance, Information, Economy, Control, Efficiency, and Service, was employed to evaluate service quality. Using a descriptive-quantitative approach and purposive sampling, data were collected from 100 respondents in the context of an evaluative research study. The results were analyzed using IBM SPSS 25. Descriptive analysis indicates that the overall service quality of the e-Perpus Kota Depok application is categorized as satisfactory. This is reflected in high average scores, particularly for the Economy (4.45) and Performance (4.44) dimensions. These findings suggest that the application effectively meets users' needs and expectations regarding service quality.